Action of Phenethyl Alcohol on the Synthesis of Macromolecules in Escherichia coli - Prevost, C. (1966)
Prevost, C. (University of California, Berkeley), and V. Moses. Action of phenethyl alcohol on the synthesis of macromolecules in Escherichia coli. J. Bacteriol. 91:1446–1452. 1966.—A kinetic study of the effects of various concentrations of phenethyl alcohol on the synthesis of ribonucleic acid (RNA), deoxyribonucleic acid (DNA), protein, and β-galactosidase in Escherichia coli has confirmed that RNA synthesis, rather than DNA synthesis, is first and most affected by phenethyl alcohol. The presence of inducer did not protect β-galactosidase synthesis from inhibition by phenethyl alcohol. Little preferential inhibition of β-galactosidase synthesis was observed; this is in contrast to the severe catabolite repression which results from partial inhibition of total protein synthesis caused by chloramphenicol or starvation for a required amino acid. We found no evidence that messenger RNA synthesis was inhibited to a greater extent than total RNA synthesis.